Penerapan ERP dan Supply Chain Management di Penginapan Homstay Batam - Yulfiswandi; Immanuel Zai; Chanda Vedalla Putra; Charles Tan; Jason; Johanes Prawira; Ng Thian Way; Steven (STEKOM PRESS, 2023)
This writing discusses Homstay Batam, an inn located in Batam City, Riau Islands. The author chose Homstay Batam as a case study because the lodging business as a service company has a different resource supply chain flow than a product company. Enterprise Resource Planning and Supply Chain Management are the main focus in this paper, where supply chain is the management of various activities to obtain raw materials that are transformed into a product in a process and continued with delivery to consumers through distribution. The stages in supply chain management include planning, process, production, storage, delivery, and return of goods. Enterprise Resource Planning is implemented with the help of social media. It is concluded that Homstay Batam has done the right division and distribution of resource planning so that the business can run optimally and generate maximum profit.